Parameters of Disavowal (Volume 1.0) - Jinsoo, An (University of California Press, 2018)
The colonial experience of the early twentieth century shaped Korea's culture and identity, leaving a troubling past that was subtly reconstructed in South Korean postcolonial cinema. Relating postcolonial discourses to a reading of Manchurian action films, kisaeng and gangster films, and revenge horror films, Parameters of Disavowal shows how filmmakers reworked, recontextualized, and erased ideas and symbols of colonial power. In particular, Jinsoo An examines how South Korean films privileged certain sites, such as the kisaeng house and the Manchurian frontier, generating unique meanings that challenged the domination of the colonial power, and how horror films indirectly explored both the continuing trauma of colonial violence and lingering emotional ties to the colonial order. Espousing the ideology of nationalism while responding to a new Cold War order that positioned Japan and South Korea as political and economic allies, postcolonial cinema formulated distinctive ways of seeing and imagining the colonial past.